Using Euler-Lagrange Equation In Solving Isoperimetric Problems (مجلة المنصور, 2023)
Many applications of calculus of variation lead to problems in which not only boundary conditions, but also conditions called subsidiary are imposed on the extreme curve. These problems are known as Isoperimetric problems. The paper will discuss these problems and derive the special Euler- Lagrange equation which is used to solve such problem with some application.